Kemampuan Menyimak Teks Cerita Fantasi Siswa Kelas VII - Ayu Sundari; Supriyadi Supriyadi (UIR Press, 2023)
This research was motivated by the ability of Class VII students in listening to fantasy story texts to find intrinsic elements from fairy tales that were read and listened to at MTs Ikhlasiyah Rokan Hilir. The 2013 curriculum includes text-based learning. This means that students are required to be able to produce a text through writing and listening skills. One of the various types of texts is fantasy story text. Fantasy story is a form of imaginary story or author fantasy that does not occur in the real world. This study aims to analyze the listening ability of seventh grade students to find the intrinsic elements of the fairy tales that are heard at MTs Ikhlasiyah from the text of fantasy stories that are read and listened to. This research is a quantitative research. This study uses a saturated sample, that is, all of the population is used as a sample and is also known as a census. All populations were sampled in the study, namely 32 students of class VII MTs Ikhlasiyah Rokan Hilir. The data analysis technique used by the researcher in this study is as follows: to examine the test results. The answer to the objective choice questions is only one correct answer. Each correct answer gets a value of 1 and the number of correct answers is added up and divided by the total number of questions (20), then multiplied by one hundred, then the student's ability to identify the intrinsic element of each individual student is obtained. From the findings of this study, it was concluded that the short story listening skills of class VII students at MTs Ikhlasiyah Rokan Hilir were in the sufficient category, with a percentage of 60.20%. The highest average of students' listening skills based on the intrinsic elements of fantasy story texts is the character/characterization element with an average value of 71.48, and the second highest is the background element with an average value of 70.31. This shows that most of the students' listening skills are in the sufficient or moderate category and the lowest student listening category is found, especially on the intrinsic elements of language style with an average value of 23.44.